(untitled) (Research, Society and Development, 2022)
Juiz de Fora, in Minas Gerais, played an important role in the transit of precious minerals between Ouro Preto and Rio de Janeiro during the 18th century. This path determined the beginning of the city and its development, being guided by the banks of the Paraibuna River, which runs through its entire urban extension and, currently, is highly polluted and has been losing its historical and leisure significance for the population. What is the role of the river in the development of the city and its importance for the residents? The objective of the work is to analyze the evolution of the occupation of the city and the function of the river in the local social memory. The specific objectives are given by the intervention project proposal as a response to the presented problem. As a methodology, documental research was implemented on the urban development of Juiz de Fora, based on the English School of Urban Morphology in Conzen (1998); and subsequent proposals for environmental intervention in the studied stretch. The results consist of the description of the urban occupation process in the study clipping, and the proposal to implement an ecological corridor along the river’s path as a way of rescuing historicity and resignification. The work emphasizes the importance of the Paraibuna axis in the study as a vector of urban development of the city and its ecological and leisure potential for the population.